TINGKAT INKLUSI KEUANGAN SEKTOR PERBANKAN PADA MASYARAKAT DI KECAMATAN TELUK SEGARA KOTA BENGKULU - Jansen Lionardo; Dewi Rahmayanti (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Abstract: This Study aims to analyze how the financial inclusion levels of people in the District Teluk Segara Bengkulu City. This study used questionnaires distributed a total of 300 questionnaires and only 288 questionnaires that can be used. The data analysis method is descriptive statistics. Financial inclusion level of respondens was low. The results showed the level of financial inclusions community in District Teluk Segara Bengkulu City, throught indicator of financial inclusions, banking penetration and use of banking service. The questionnaires of this study use OECD/INFE Toolkit For Measuring Financial Literacy and Financial Inclusions 2015.Keyword: Financial Inclusions, Society in District Teluk Segara Bengkulu City.